FRI0398 Disease Specific Quality of Life in Patients with Lupus Nephritis. (10th June 2014) - Jolly, M.; Toloza, S.; Bertoli, A.; Blazevic, I.; Vila, L.; Moldovan, I.; Torralba, K.; Kaya, A.; Goker, B.; Tezcan, M.; Haznedaroglu, S.; Bourre-Tessier, J.; et al.
Abstract : Background: Little is known about patient reported outcomes (PRO) in lupus nephritis (LN), and no studies using a disease targeted PRO tool have been undertaken thus far. Objectives: To describe quality of life (QOL) among patients with LN using a valid and reliable disease targeted PRO measure (LupusPRO). Methods: Cross sectional data obtained from patients with systemic lupus erythematosus (SLE) during psychometric evaluation studies of LupusPRO from various countries were compared between those: 1) with and without LN and 2) with active and inactive-LN." Data compared included demographics, disease characteristics, and LupusPRO constructs. Presence of LN was present if listed among the ACR classification criteria (ACR-LN), while presence of active LN was based on presence of urinary casts, hematuria, proteinuria or pyuria in the disease activity assessment (SELENA-SLEDAI) performed at the time of the study visit. LupusPRO has Health related QOL (HRQOL) and non-HRQOL constructs. HRQOL domains include lupus symptoms, cognition, medication, procreation, physical health, emotional health, pain-vitality and body image. Non-HRQOL domains include desires-goals, social support, coping and satisfaction with care. Non-parametric tests were used to make comparisons, and p values ≤0.05 were considered significant. Results: There were 1, 259 SLE patients; ninety-four percent were women and their mean (SD) age was 41.7 (13.5) yrs. Five-hundred and thirty-nine had ACR-LN. These patients were younger, had greater disease activity (PGA, Total SELENA-SLEDAI) and damage (SLICC/ACR) than those without LN. Summary HRQOL and non-HRQOL scores were similar in both groups; however, those with ACR-LN had significantly worse scores on medications and procreation domains, while those without ACR-LN had worse scores on Pain-Vitality domains. 129/540 ACR-LN patients had active LN. Patients with active LN were younger, had significantly greater disease activity (PGA, Total SELENA-SLEDAI), worse HRQOL and non-HRQOL than patients with inactive LN. Specific domains scores adversely affected among active LN patients were lupus symptoms, medications, procreation, emotional health, body image and desires-goals. Satisfaction with care was significantly higher among patients with active LN as compared to inactive LN patients. Conclusions: LN adversely affects several specific QOL domains and physicians need to be aware of these concerns Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3775